Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Website dengan Metode Prototype (Studi Kasus: SMK Mitra Bintaro) - Melyana Sofianti; Mufidah Karimah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The new student registration process, which is still carried out using conventional methods, makes the process feel slow and inefficient. In addition, relying on paper documents can lead to data loss or damage, and disorganized registration data can make it difficult for staff to manage and retrieve information about prospective students. These problems emphasize the necessity to create a more efficient and automated system. This research intends to create and develop an online New Student Admission Information System to help staff handle applicant information and minimize the number of applicants visiting the school in person. The Prototype method is the system development approach employed, facilitating ongoing interaction and assessment between users and developers. The findings of the research show that the created system streamlines the registration process, data handling, administration of entrance exams, management of selection results, and re-registration payments enhancing their efficiency, speed, and transparency. By implementing this system, the new student admission procedure is streamlined and reduces mistakes in data management.